A microcomputer controller for a nylon spinning machine - Kirk, Terence Enfield (Department of Electrical Engineering, 2023)
This thesis will show how a new type of controller for a Nylon spinning machine was developed from an initial specification. The controller is a component in a loosely coupled feedback system which reads two tachometer pulse trains and various plant interlocks and produces two pulse trains which are used to control two solid state variable frequency variable voltage inverters and their AC motors. The specification calls for 24 controllers to be linked to a PDP 11/23 host computer which holds a library of operating parameters which can be downloaded into each control unit by ~n operator. After examining the requirements of the system, a microcomputer implementation was chosen as· best meeting the needs of the project. Elsewhere in the plant several earlier attempts at using micro-computers as dedicated controllers had been made, with rather poor results. Consideration of the future requirements of the company showed that there was a clear role for these controllers, and it was clear that there was a need to define standards for their development and implementation, and so a survey of the company's requirements was done, on the basis of which a standard was adopted. The thesis covers ali system related aspects of the project, from the initial selection of a microcomputer system and software development system to the design and implementation of the controller.